Doomed to fail: the persistent search for a modernist mental health nurse identity - Hurley, John (Nursing philosophy, 2009)
The perennial issue of the distinctiveness of the mental health nurse (MHN) is once again to the fore. Previous attempts to resolve this apparent identity crisis in the discipline have included proposals for new models, new research and new educational preparation as well as new alliances, and new ways of practising. Now the politically driven concept of the generic nurse is gaining enough momentum to potentially end the discussion once and for all. This paper takes a postmodernist approach to MHN identity that questions the requirement for MHNs to articulate their distinctiveness, and offers alternative constructions of this identity to those promulgated by policy makers and by other health disciplines.